Pendampingan Kegiatan Dasawisma dan Implementasi Barcode untuk Identifikasi Tanaman pada Pengelolaan Dasawisma Desa Sikalang, Kecamatan Talawi, Kota Sawahlunto - Zahra, Nabila Aliyah; Linda Marni; Maulana Arifin; Tara Rizkyka; Yuni Safira; Uly Adela Rahma (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this activity is to provide understanding and practical skills to Dasa Wisma cadres in utilizing simple technology in the form of barcodes as a tool for plant identification, while also improving the documentation system that was previously carried out manually. The methods of implementing the activity include socialization, technical training on creating and scanning barcodes, as well as field assistance. Data collection techniques are conducted through direct observation during the activity, brief interviews with Dasa Wisma cadres, and documentation of plant data before and after the implementation of barcodes. The data analysis technique used is qualitative descriptive. The results indicated an improvement in the cadres’ ability to digitally identify and document plant data, thereby simplifying the data collection process and accelerating access to plant-related information. The barcode implementation also contributed to more organized, accurate, and easily traceable data. Overall, this program strengthened Dasa Wisma administrative management and encouraged the adoption of simple digital technology in environmental management at the community level. These findings demonstrate that digital-based innovations can be effectively implemented at the village level and have a positive impact on the sustainability of Dasa Wisma management.